Design for Low-Cost Country Sourcing: Motivation, Basic Principles and Design Guidelines - Lanza, G.; Weiler, S.; Vogt, S. (Cranfield University Press, 2009)
Not every product can be successfully sourced in low-cost countries. Disadvantageous cost structures or extremely complex workpiece designs are the most frequent reasons for failures. A design that has been tailored to low-cost country sourcing offers the possibility of increasing potentials while reducing risks and costs at the same time. The wbk Institute of Production Science at the Universität Karlsruhe (TH) developed a new approach which ensures that the product design meets the requirements of the supplier. This paper identifies the factors influencing the design, deduces basic principles and illustrates guidelines for an adapted product design.
Organised by: Cranfield University
Keywords: Design for X; Low-Cost Countries; Global Sourcing; Product Development